Identification and investigation of properties of social support - MacIntosh, Nancy J. [Verfasser] (My University, 1991)
"In response to the charge by House and Kahn (1985) that there is lack of specificity in conceptualization and measurement of the social support construct, this paper suggests the need to identify and specifically measure discrete properties of the previously identified dimensions (type and source) of social support. Properties are defined as what it is about combinations of source and type that needs to be measured. Based on literature reviews it is suggested that the relevant properties are amount of support, adequacy of support and number of provieders of support. Measures are developed for each property. Data from 186 nurses were used to assess main and moderating effects of social support properties, workload and dying patients on emontional exhaustion and physical symptoms." (author's abstract) ((en)) Das Papier befasst sich mit der Konzeptualisierung und Messung von sozialer Unterstützung. Dabei sollen vor allem die Eigentümlichkeiten sozialer Unterstützung herausgearbeitet werden, die sich aus der Art (sozioemotionale, instrumentelle) und der Quelle (z.B. Vorgesetzter, Kollegen, Familie) der Unterstützung ergeben. In einer Befragung von 186 Krankenschwestern wurde untersucht, wie sich diese Eigenheiten sozialer Unterstützung nebst Arbeitsbelastung und Patientensterben auf die gefühlsmässige Verausgabung und physischen Symptome auswirken. (IAB)
Identifizierung und Untersuchung der Eigentümlichkeiten von sozialer Unterstützung
Keywords: T 4.8 Arbeitswissenschaften; S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 2.4 Sozialer Wandel; T 4.8 Arbeitswissenschaften; Soziale Beziehungen; Einflussfaktor; Arbeitsbelastung; Krankenschwester; Auswirkung; Physische Belastung; Psychische Faktoren; Berufsproblem; Quantitative Angaben